An integrated RNA sequencing and network pharmacology approach reveals the molecular mechanism of dapagliflozin in the treatment of diabetic nephropathy - Bai, Zhenyu; Xie, Ting; Liu, Tianhao; Chen, Zedong; Yu, Linde; Zhang, Chao; Luo, Jincheng; Chen, Liguo; Zhao, Xiaoshan; Xiao, Ya (Frontiers in Endocrinology, 2022)
Dapagliflozin, an inhibitor of sodium-glucose cotransporter 2 (SGLT2), is a novel class of oral hypoglycemic drugs that promote glucose excretion in the kidney. Studies have shown that dapagliflozin has renoprotective effect in the treatment of type 2 diabetes. However, the underlying mechanism remains unclear. Here, we combined integrated RNA sequencing and network pharmacology approach to explore the molecular mechanism of dapagliflozin in the treatment of diabetic nephropathy (DN). Dapagliflozin significantly relieved glucose intolerance, urinary albumin/creatinine ratio (UACR) and renal pathological injuries of db/db mice. The lncRNA and mRNA expression in kidney tissues from control group (CR), db/db group (DN) and dapagliflozin group (DG) were assessed by RNA sequencing. We identified 7 LncRNAs and 64 mRNAs common differentially expressed in CR vs DN and DN vs DG, which were used to construct co-expression network to reveal significantly correlated expression patterns in DN. In addition, network pharmacology was used to predict the therapeutic targets of dapagliflozin and we constructed component-target-pathway network based on the data of RNA sequencing and network pharmacology. We found that SMAD9, CASP3, H2-DMB2, MAPK1, MAPK3, C3, CYP4A12A, CYP4A12B, CD36, PPARG, and IL-10 might be the key targets for Dapagliflozin in the treatment of DN and these genes were mainly enriched in pathways including TGF-β signaling pathway, PPAR signaling pathway, Chemokine signaling pathway, etc. Our results have important implication and provide novel insights into the protective mechanism of dapagliflozin in the treatment of DN.